Coupling the effects of extreme temperature and air pollution on non-accidental mortality in Rencheng, China - Yu, Daozheng; Lee, Soo-Beom; Chen, Si; Kim, Seong Wook; Xi, Shuaishuai (Frontiers in Public Health, 2023)
Extreme temperatures and air pollution have raised widespread concerns about their impact on population health. To explore the quantitative exposure risks of high/low temperatures and types of air pollutants on the health of various populations in urban areas in China, this study assessed the effects of temperature and air pollutants on daily non-accidental deaths in Rencheng District, Jining City, China from 2019 to 2021. A combination of Poisson regression models and distributed lag non-linear models was used to examine the relationships between temperature, air pollutants, and daily non-accidental deaths. We found that temperature and air pollutants had a significant nonlinear effect on non-accidental mortality. Both high and low temperatures had a noticeable impact on non-accidental deaths, with heat effects occurring immediately and lasting 2-3 days, while cold effects lasted for 6-12 days. The relative risks of non-accidental deaths from PM2.5, NO2, and SO2 were highest in winter and lowest in autumn. The relative risk of non-accidental deaths from O3 was highest in spring, with no significant variations in other seasons. Elderly people (≥75) and outdoor workers were at the greatest risk from temperature and air pollutant exposure. Exposure to extreme temperatures and air pollutants in the Rencheng District was associated with an increased mortality rate. Under the influence of climate change, it is necessary for policymakers to take measures to reduce the risk of non-accidental deaths among residents.